2008
DOI: 10.1152/ajpheart.321.2008
|View full text |Cite
|
Sign up to set email alerts
|

Basal and IGF-I-dependent regulation of potassium channels by MAP kinases and PI3-kinase during eccentric cardiac hypertrophy

Abstract: The potassium channels IK and IK1, responsible for the action potential repolarization and resting potential respectively, are altered during cardiac hypertrophy. The activation of insulin-like growth factor-I (IGF-I) during hypertrophy may affect channel activity. The aim was to examine the modulatory effects of IGF-I on IK and IK1 through mitogenactivated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) pathways during hypertrophy. With the use of specific inhibitors for ERK1/2 (PD98059), p38 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…Thus, we examined the electrophysiological role of insulin-like growth factor-1 (IGF-1) in the present study since this growth factor has been shown to exert significant antioxidant and antiapoptotic effects on the myocardium (18,36,39,44). As shown in Figure 3A, 10 nM IGF-1 for 4-5 h upregulated I to density in myocytes from MI hearts (filled squares) to a similar extent as JNK=p38 inhibitors.…”
Section: Redox-mediated Remodeling Of K + Channels 27mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we examined the electrophysiological role of insulin-like growth factor-1 (IGF-1) in the present study since this growth factor has been shown to exert significant antioxidant and antiapoptotic effects on the myocardium (18,36,39,44). As shown in Figure 3A, 10 nM IGF-1 for 4-5 h upregulated I to density in myocytes from MI hearts (filled squares) to a similar extent as JNK=p38 inhibitors.…”
Section: Redox-mediated Remodeling Of K + Channels 27mentioning
confidence: 99%
“…3). It is possible that the lack of Kv channel remodeling in sham hearts by IGF-1 is related to unique cellular responses to acute versus sustained activation of ASK1-JNK-p38 signaling (12,18,39,40). It is also possible that distinct isoforms of JNK or p38 (26,31,34) are involved in Kv channel downregulation that are activated by pathogenic (e.g., angiotensin II and endothelin) but not physiologic (e.g., IGF-1) stimuli.…”
Section: Igf-1 Effects In Sham Heartsmentioning
confidence: 99%
“…In addition, ERK1/2 can phosphorylate and modulate the activity of Na + /H + exchanger 1 (NHE-1), which is indirectly involved in Ca 2+ regulation in the heart (Moor and Fliegel, 1999). Inhibition of ERK1/2 also significantly reduced the K + channels ( I K and I K1 ) activity in hypertrophied adult cardiomyocytes (Teos et al, 2008). …”
Section: Mapks In Chronic Cardiac Stress (Hypertrophy and Heart Famentioning
confidence: 99%
“…Acute treatment of rat ventricular myocytes with IGF-1, induction of volume-overload cardiac hypertrophy (which is associated with increased IGF-1 signaling and Akt activation) or adenoviral expression of Akt or constitutively active PI3K in rat neonatal cardiomyocytes were all reported to decrease the delayed rectifier current I K and the inward rectifier I K1 . 76, 77 On the other hand, repolarizing potassium currents in ventricular myocytes were upregulated in two models of physiological hypertrophy, one produced by cardiac-specific expression of constitutively active p110α and the other by swim training. 78 Protein and/or mRNA expression of numerous potassium channel subunits was also increased (Fig.…”
Section: Voltage-dependent Potassium Channelsmentioning
confidence: 99%